2009
DOI: 10.1002/app.31114
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinking and thermal stability of thermosets based on novolak and melamine

Abstract: ABSTRACT:The crosslinking under pressure of a mixture of novolak with melamine resin has been investigated by means of several techniques, including differential scanning calorimetry, thermal gravimetric analysis, X-ray diffraction, and infrared spectroscopy. The crosslinking of the mixture essentially follows two steps. The former occurs at 150 C and leads to resin networks composed of di-and trisubstituted phenols without significant reaction with melamine polymers. The latter, at 200 C, mainly involves the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 19 publications
0
14
0
2
Order By: Relevance
“…Spectra of CNTCOOH and CNTFA exhibit a peak at about 26°corresponding to the graphite (002) reflection [37,38]. In the case of CNTFA/novolac composites, the amorphous peak at around 19.4°is a characteristic of phenolic resin [39]. According to the fact that there is not any peak other than CNTFA and amorphous novolac in the XRD patterns of RCNTFA2, RCNTFA4, and RCNTFA6, it can be concluded that CNTFA is dispersed homogeneously in the novolac matrix.…”
Section: Resultsmentioning
confidence: 97%
“…Spectra of CNTCOOH and CNTFA exhibit a peak at about 26°corresponding to the graphite (002) reflection [37,38]. In the case of CNTFA/novolac composites, the amorphous peak at around 19.4°is a characteristic of phenolic resin [39]. According to the fact that there is not any peak other than CNTFA and amorphous novolac in the XRD patterns of RCNTFA2, RCNTFA4, and RCNTFA6, it can be concluded that CNTFA is dispersed homogeneously in the novolac matrix.…”
Section: Resultsmentioning
confidence: 97%
“…Phenolic resins are preferred for aircraft interiors due to the extraordinary fire, smoke, and toxicity characteristics. Due to their excellent ablative properties, they are also used to manufacture carbon–carbon composites, rocket nozzles and heat shields . However, the major shortcoming is the evolution of volatiles during high temperature curing, which necessitates application of expensive processing equipment like autoclave, hydroclave, or hot press .…”
Section: Introductionmentioning
confidence: 99%
“…According to the results, narrow and sharp diffraction peaks of CNTCOOH and CNTFA appeared at 26.18 and 44.28 indicating graphite (002) and (101) reflections [34][35][36]. In the spectra of CENR and CENC2, the broad amorphous diffraction peak of phenolic resins was appeared around 208 [37]. Additionally, characteristic peaks of CNTFA were not observed in the spectrum of CENC2 which may be due to the uniform dispersion of CNTFA in the ENR matrix [13].…”
Section: Resultsmentioning
confidence: 99%